Insurance Transitions Following the First ACA Open Enrollment Period - Carman, Katherine Grace (RAND Corporation, 2015)
While most of the Affordable Care Act's coverage-related provisions took effect in January 2014, there is limited information on insurance transitions that occurred in the period before and after these changes became operational. This report examines insurance transitions between September 2013 and November 2014 using longitudinal data from the RAND Health Reform Opinion Study.